Assessment of clinical profile of patients with non-radiographic axial spondyloarthropathy in a tertiary health-care center - Saurabh Limaye; Shraddha More; Milind Nadkar; Alhad Mulkalwar; Hunaid Haider; Sujay Jaju (Asian Journal of Medical Sciences, 2022)
Background: Axial spondyloarthritis (nr-axSpA) is an inflammatory and immune-mediated condition comprising clinically differentiated ankylosing spondylitis (AS) and nonradiographic nr- axSpA. Clinically, as the name suggests, non-radiographic nr- axSpA has an absence of definitive plain X-ray evidence of structural damage to the sacroiliac joint.